IMPLEMENTASI PEMBELAJARAN BLENDED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PEMBUATAN MAKANAN KONTINENTAL DI SMK PIUS X MAGELANG - Mahanani, Thyara; Hamidah, Siti (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study aims to determine: (1) the application of Blended learning to improve motivation and learning outcomes of students on the subjects of Continental, (2) the implementation of learning continental food that uses Blended learning to improve motivation and student learning outcomes, and (3) the opinion of students towards learning using Blended Learning to increase motivation and student learning outcomes. This research is a classroom action research method observing and learning activities a group of students by giving actions which intentionally raised. Subjects in this study were students of class XI Tata Boga 1, SMK PIUS X Magelang with the number of 40 students as subject of research. Data collection using observation, documentation, tests,and questionnaires.Data analysis techniques using quantitative descriptive.The results showed that: (1) the method of Blended Learning using Web media of Learning can improve motivation and learning outcomes of students of class XI Tata Boga SMK PIUS X Magelang, (2) Students who demonstrate increased activity of high learning from the first Cycle to 90%, and (3) students ' Opinions related to Web media Learning used in the learning activities the majority of the students expressed interest (for 82.5%).